Pengaruh Kepribadian terhadap Perilaku Manajemen Keuangan dengan Literasi Keuangan sebagai Variabel Intervening - Nurfadillah, Nurfadillah; Rusnawati; MS, Eka Indriyani (Study of Scientific and Behavioral Management, 2024)
ABSTRACT The purpose of the research was to find out whether there was an influence of personality towards financial management behavior with financial literacy as intervening variable in micro small and medium enterprises in Makassar. The objective of the research was the subject of micro small and medium enterprises (UMKM) in Makassar. The research conducted quantitave design. The samples of the research were 160 UMKM registered in economic enterprises and UKM official of Makassar. The sampling techniques used was non probability sampling used to give equal chance or opportunity for every member of population to be selected as a sample. The clarity level of the research used associatif problem statement to find out the correlation or influence between two or more variables. The data used were primary and secondary data where the data was collected by using questionnaire, observation and bibliography study. Data analysis used qas PLS (Partial Least Square). The research result shown that there was positive influence of personality towards financial management, there was positif ilnfluence of personality towards financial literacy, there was postitive influence of personality towards financial management behavior, and also there was positive influence of personality towards financial management behavior with financial literacy as intervening variable. Keywords: Personality, Financial Management Behavior, and Financial Literacy